(untitled) (Nepal Journal of Environmental Science, 2025)
Zooplankton studies and observation are useful for managing the physio-chemical and biological environment of the aquatic ecosystems, thus playing a vital role in fisheries. Seasonal variations affect the physio-chemical variables thus causing variation in abundance and diversity of plankton. Zooplankton samples were collected from Phewa, Begnas, Rupa, Khaste, Dipang, Neureni, Maidi and Gunde lakes in the month of November 2023 (Post- monsoon) and April 2024 (Pre-monsoon). A total of 33 species of zooplankton with 5 groups, comprising Rotifer (23), Copepod (4), Cladocera (3), Protozoa (2), and Cnidarians (1) were recorded from the lakes of Pokhara Valley. Comparatively, the mean zooplankton abundance was significantly higher (p <0.05) in Rupa Lake and was with the highest species richness in post-monsoon. The value of the Shannon-Wiener Index (H’) ranged from 1.26 - 2.75 indicated moderate pollution in lakes, whereas Pielou’s Species Evenness (J) less than 0.5 indicated the presence of ecological stress in all lakes except in Begnas Lake. Rotifers were abundant in all lakes over both seasons, indicating changing lake’s condition. It is important to prevent nutritional load on water quality parameters during the urbanization process and agrochemicals to increase zooplankton stability and diversity in these lakes.